2021
DOI: 10.36497/respirsci.v1i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Pneumoconiosis in Limestone Mining Workers In Citatah Village, West Bandung District

Abstract: Background: Silica, asbestos and coal dust are associated with pneumoconiosis in mining workers. The International Labor Organization (ILO) reports that 30-50% of workers in developing countries are diagnosed with pneumoconiosis. This study aims to identify pneumoconiosis in limestone mining workers in Indonesia. Method: This cross-sectional study involved 73 subjects of limestone mining workers in Citatah Village, West Bandung Regency, Indonesia. Two conclusions were similar from three AIR-Pneumo certif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The study found that dust concentration was highest at the mining site in pneumoconiosis group compared to the mining site of the non-pneumoconiosis group. The study also showed that the duration of labor and the concentration of mining site's dust are risk factors for lung disease [14]. Researchers carried out a study to determine the correlation exposure of particulate matter (PM2.5) with lung function impairment in LSI's workers.…”
Section: Review Of Some Previous Studiesmentioning
confidence: 99%
“…The study found that dust concentration was highest at the mining site in pneumoconiosis group compared to the mining site of the non-pneumoconiosis group. The study also showed that the duration of labor and the concentration of mining site's dust are risk factors for lung disease [14]. Researchers carried out a study to determine the correlation exposure of particulate matter (PM2.5) with lung function impairment in LSI's workers.…”
Section: Review Of Some Previous Studiesmentioning
confidence: 99%
“…al. [10] and Wellid et al [11]. One of the early indicators that air pollution has occurred in an area is the high number of ARI cases [8], [9], [11].…”
Section: Introductionmentioning
confidence: 99%